Большая игра: [роман] / Татьяна Устинова - Устинова Татьяна Витальевна (Детектив, 2003)
Экземпляры: ф.12 (2003) / Инвентарный номер: 44792 / Цена: / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: У 80 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44